2010
DOI: 10.1159/000313506
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Hydrogel Sustains the Delivery of Dexamethasone across the Round Window Membrane

Abstract: Background: The use of intratympanic (IT) steroids for the treatment of inner ear disorders is promising, but the clinical challenges of prolonged middle ear drug application have proven burdensome, and a sustainable delivery system is yet to be developed. Method: In this study, a guinea pig model was used to determine if dexamethasone in combination with a hyaluronic-acid (HA)-based hydrogel is an efficient, stable and sustainable dexamethasone delivery system to the inner ear. For each animal, right and left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 99 publications
2
57
0
Order By: Relevance
“…The measured perilymph drug levels both in this study and those reported by Wang et al [2009] with similar methodology show less variability than prior studies with dex solutions [Parnes et al, 1999;Chandrasekhar et al, 2000;Hahn et al, 2006;Plontke et al, 2008a;Borden et al, 2010]. This is possibly the result of the longer residence time of the drug solution in the middle ear or the sustained drug level provided by the slowly dissolving micronized dex suspension.…”
Section: Discussionsupporting
confidence: 64%
“…The measured perilymph drug levels both in this study and those reported by Wang et al [2009] with similar methodology show less variability than prior studies with dex solutions [Parnes et al, 1999;Chandrasekhar et al, 2000;Hahn et al, 2006;Plontke et al, 2008a;Borden et al, 2010]. This is possibly the result of the longer residence time of the drug solution in the middle ear or the sustained drug level provided by the slowly dissolving micronized dex suspension.…”
Section: Discussionsupporting
confidence: 64%
“…There have been numerous pharmacokinetic studies of locally-applied corticosteroids in animals (Nomura 1984;Parnes et al 1999;Chandrasekhar et al 2000;Bachmann et al 2001;Hahn et al 2006Hahn et al , 2012Liu et al 2006;Plontke et al 2008b;Yang et al 2008;Wang et al 2009;Borden et al 2011;Salt et al 2011a) and humans (Bird et al 2007;Bird et al 2011), but only a subset of these studies has been analyzed quantitatively to derive an elimination rate. Plontke and analyzed prednisoline data of Bachmann et al (2001) from guinea pigs and found it to be consistent with an elimination half-time from perilymph of 130 min.…”
Section: Introductionmentioning
confidence: 99%
“…Agents such as histamine and hyaluronic acid have been shown to facilitate transport of the corticosteroid across the round window membrane in laboratory studies [22,23]. Intratympanic corticosteroids appear to affect both immune suppression and ion homeostasis [24].…”
Section: Discussionmentioning
confidence: 99%
“…A 1.5 -2.0 mm microcatheter was placed into the niche and connected to a continuous infusion pump with methylprednisolone (62.5 mg/mL) delivered for 14 days at a rate of 10 microliters per hour 83% of these had improved SDS with 66% returning to normal hearing Borden RC, et al [23] Microcatheter placed near roun window and they perfused methylprednisolone (62.5 mg/ml) continuously at 10 µl/h for 10 d…”
Section: Discussionmentioning
confidence: 99%